The Establishment of Child Health Cadre as Prevention for Foodborne Disease at Primary Schools - Fariani Syahrul; Chatarina U. W.; Arief Hargono (International Journal of Public Health Science (IJPHS), 2017)
Personal health, including health on school-age children comes from food intake. But often, these foods can cause health problems, such as foodborne diseases. A quasi-experimental study was conducted to monitor the Clean and Healthy Lifestyle (CHL) of children at school through the establishment and evaluation of child health cadres. Phases of activities are the selection of child health cadres (10 children), training and determination of the child that will be monitored (40 children), preliminary assessment on the monitored CHL, two-month monitoring and final assessment. Monitored CHL are the CHL associated with foodborne diseases such as clean nails, snacks habit, habit of bringing lunch, and hand-washing habit in schools. Descriptive analysis showed that there were differences between the CHL school children before and after the monitoring conducted by child health cadres, however the results of the Chi-Square Test indicated that only the habit of bringing lunch that yield a significant change  (p=0.01). Evaluation of the routine activity showed that the average cadre activity on monitoring is 75.7% and the average of completeness monitoring books is 91.9%. The activities of child health cadres can be applied on an ongoing basis with the school health program activities that have been established in schools.